Protection Effect of Self-Nanoemulsifying Drug Delivery System (SNEDDS) Piroxicam as Ulcerogenic Agent towards Malondialdehid Level and Protein Expression of Caspase-3, COX-1, COX-2 at Rat Gastric - Iis Wahyuningsih; Kurnia Ambarwati; Erninda Ayu Hapsari; Afifah Fauziyyah; Azis Ikhsanudin; Deasy Vanda Pertiwi; Wahyu Widyaningsih (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2020)
The aim of this study was to determine the protection effect of SNEDDS piroxicam ulcerogenic agent against malondialdehyde (MDA) level and protein expression of caspase-3, COX-1, COX-2. The research was conducted using the test animals as much as 30 male white Sprague dawley (SD) rats aged 1-2 months with a weight of 100-200 grams divided into 5 groups. Treatment was given for 28 days orally. On the 29th day blood samples were also taken for the determination of MDA (Malondialdehid) levels by Thiobarbituric Acid Reactive Substance (TBARs) method using a visible spectrophotometer. Rats were sacrificed, then gastric organs were taken for immunohistochemical testing of caspase-3 and COX-1 expression, COX-2. The statistical analysis showed that the piroxicam SNEDDS group and the piroxicam suspension group decreased expression of the caspase-3 protein, increased COX-1 expression, decreased COX-2 and significantly decreased MDA levels. The piroxicam-containing SNEDDS (Self-Nanoemulsifying Drug Delivery System) form has protection against ulcogenic piroxicam.